A Novel Layered Learning Approach for Forecasting Respiratory Disease Excess Mortality during the COVID-19 pandemic - Ashofteh, Afshin (2021)
Ashofteh, A., Bravo, J. M., & Ayuso, M. (2021). A Novel Layered Learning Approach for Forecasting Respiratory Disease Excess Mortality during the COVID-19 pandemic. In CAPSI 2021 Proceedings : 21ª Conferência da Associação Portuguesa de Sistemas de Informação, "Sociedade 5.0: Os desafios e as Oportunidades para os Sistemas de Informação".[21th Portuguese Association of Information Systems Conference] (pp. 1-18). Associação Portuguesa de Sistemas de Informação. ----- The authors are grateful to the anonymous reviewers for their constructive comments. Their critical and constructive remarks were precious to improve the final paper. Jorge M. Bravo was supported by Portuguese national science funds through FCT under the project UIDB/04152/2020-Centro de Investigação em Gestão de Informação (MagIC). Additionally, M. Ayuso is grateful to the Secretaria d’Universitats i Recerca del departament d’Empresa i Coneixement de la Generalitat de Catalunya for funding received under grant 2020-PANDE-00074. It’s a research project directly related to COVID and economy.